Sindicatos dos trabalhadores bancários: formações discursivas em concorrência - Silva Neto, Antonio Artequilino da (2018)
This Doctoral Thesis, linked to the line of researches Language and Work, aims at analysing the interdiscursive relationship that involves and constitutes the Banking Workers Unions of São Paulo and Santos discourses. Both trade unions represent the banking category in their bases, with the purpose of protecting their economic and labour interests. A historical analysis of the Banking Union Movement reveals the course of struggles undertaken over the time and its consequences in the present days. Changes in the world of work keep happening and they include transformations in the Brazilian banking industry that currently promotes structural changes, which affect employment and working conditions of banking workers. In this context, the role of the Banking Union Movement is played within a complex dynamic of interactions that include financial institutions, banking workers, judiciary, trade unions, government, and the population. Collective negotiations take place at the base data of the category and represent the climax of the confrontation of interests that put on opposing tables the Baking Unions and workers' representatives. This is a critical moment that reveals the discursive tensions that assume and express distinct ideological positioning in the treatment of issues involving conflicting relationships between Capital and Labour in its union, social, political, economic, and historical aspects. The central thesis of this research is proven with the prevalence of the hypothesis that the unions of bank workers of São Paulo and Santos establish among themselves a competitive relationship characterized by distinct discursive movements, while at the same time working together under the guidance of a unified national command. In addition, assume a convergence of purpose in confrontation with the bankers, although adopt different forms of resistance and opposition to the bankers, represented by the FENABAN - Banks National Federation. The theoretical basis adopted are the concepts of Discursive Ethos, Scenography, and Intersemiotic Practices, mobilized from the constraints established by Global Semantics, as conceived by Dominique Maingueneau, within the assumptions of a qualitative work. The articulation between theory and methodological procedures made possible the in-depth analysis of the corpus, delimited to the Banking Workers Union’s discourses and constituted by the newspaper “Baking News” of the Banking Syndicate of São Paulo and the “Banking Information” published by the Banking Syndicate of Santos. I collected and analysed the texts of information presented in digital media related to the ‘2015 Salary Campaign’, from August 1st to November 7th, from the first negotiations to the end of the category strike movement, which lasted 21 days and made possible the signing of Collective Instruments: Collective Labour Convention, and Collective Labour Agreements. In corpus analysis, I considered the principle of interdiscourse, focusing specifically the production of meanings in the sections in which the unions let themselves converge and those in which they demonstrate dissent